Augmentative and Alternative Communication Assessment Practices Followed in a School Setting: A Survey of Cypriot-Greek Speech and Language Pathologists - Theodorou, Elena; Pampoulou, Eliada (My University, 2022)
Objectives: Many countries throughout the world have achieved significant advances in Augmentative and Alternative Communication, whereas in Cyprus the evidence suggests that it is still in its early stages of development. The focus of this study was on assessment methods, which are the foundation for a successful intervention. Methods: For the study objectives, aspects from the participation model relating to opportunity and access barriers and existing literature on AAC assessment were used to create a questionnaire with multiple-choice answers. A total of 89 speech and language therapists working in a public school setting participated in the study. Results: The results show that AAC assessment is mainly for pupils with autism spectrum disorder. During the evaluation process, participants used various stimuli, but mostly hearing and visual, whilst using touch, smell, and taste to a much lesser extent. As part of the evaluation process, the participants reported that they focused on whether the individual could express yes/no and voice their basic needs, whereas language domains were not thoroughly assessed. Lastly, the participants focused on the ability of pupils to follow instructions, with other behaviors being assessed to a lesser extent. Conclusion: Various ideas have emerged regarding how to improve AAC assessment practices in schools.
Keywords: Augmentative and alternative communication; Complex communication needs; Speech and language pathologists; Assessment; School; Cyprus